The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201802901
|View full text |Cite
|
Sign up to set email alerts
|

Carborane‐BODIPY Dyads: New Photoluminescent Materials through an Efficient Heck Coupling

Abstract: A small library of carborane-BODIPY/aza-BODIPY dyads were efficiently synthesized by means of a novel convergent synthetic approach, the key step of which is a Pd-catalyzed Heck coupling reaction. The structural characterization and photoluminescence properties of the newly synthesized dyads were evaluated. The presence of the carborane did not significantly alter the photophysical patterns of the BODIPY or aza-BODIPY in the final fluorophores, but it produced a decrease of the emission fluorescent quantum yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…[19][20][21] . Owing to the intrinsic properties of carboranes, they have been used as exceptional building blocks for developing functional organic materials with enhanced thermal and chemical properties 22-25 . In the last decade, the development of boron cluster-based organic -conjugated systems have attracted huge interest as active materials in (opto)electronic devices, such as organic lightemitting diodes (OLEDs), organic field effect transistors (OFETs), solar cells, biological sensors and imaging, [26][27][28] among others. 29,30 It has been demonstrated the remarkable influence of the o-carborane cluster on the photophysical properties of luminescent materials in solution and solid state.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] . Owing to the intrinsic properties of carboranes, they have been used as exceptional building blocks for developing functional organic materials with enhanced thermal and chemical properties 22-25 . In the last decade, the development of boron cluster-based organic -conjugated systems have attracted huge interest as active materials in (opto)electronic devices, such as organic lightemitting diodes (OLEDs), organic field effect transistors (OFETs), solar cells, biological sensors and imaging, [26][27][28] among others. 29,30 It has been demonstrated the remarkable influence of the o-carborane cluster on the photophysical properties of luminescent materials in solution and solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that carborane-BODIPY dyads were easily internalized by HeLa cells, those bearing m-carborane clusters being the ones that show the best fluorescence characteristics for cell imaging purposes. 26 Owing to our interest to use fluorescent carborane derivatives for biological purposes, herein we have analysed the cytotoxicity and the potential use of compounds 4-6 as fluorescent probes for biological systems.…”
Section: Biological Assaysmentioning
confidence: 99%
“…Compounds 4-6 were dissolved and filtered following the same protocol as that in a previous work, 26 obtaining a final compound concentration of 10 µM and 0.5% of DMSO (Sigma/ Aldrich). 26 HeLa cells, which were routinely cultured under standard conditions, were used to analyse the cytotoxicity, the cellular uptake and the internalization pathway. 26,27…”
Section: Biological Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in carboranes and metallacarboranes as potential units for molecular materials might be endorsed to their remarkable chemical, thermal, and biological stabilities [7][8][9][10][11][12][13][14][15][16][17]. Owing to the properties above of carboranes, they have been used as exceptional building blocks for developing a large variety of fluorescent carborane-containing molecules, in which the cluster is usually linked to a fluorescent π-conjugated organic system, either directly by the C c [18][19][20][21][22][23][24][25][26][27][28][29][30] or through one spacer [7][8][9][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%